Evaluating Human Resource Planning Requirements in a Targeted Consultancy - Kománek, Jan (2025)
This thesis examines human resource (HR) capacity planning in a mid-sized Czech consulting firm, focusing on inefficiencies in current staffing practices and the potential of agile principles to improve responsiveness, fairness, and strategic alignment. Through 15 semi-structured interviews with HR professionals and consulting managers, the study explores employee perceptions of planning tools, decision-making processes, and cross-team coordination. Findings reveal a system marked by localized agility and managerial ownership but constrained by outdated tools (e.g., Excel), fragmented governance, and limited visibility into skills and forecasts. While informal agile behaviors - such as rapid resourcing and iterative planning-are already present, they remain unstructured, inconsistent, and difficult to scale across the firm. To address these issues, the thesis introduces a six-step conceptual model integrating forecasting, dynamic skills inventories, smart matching, transparent allocation, and continuous improvement. Practical, low-tech recommendations are offered to help the firm transition from reactive, manual planning toward a more strategic and adaptive system. This research contributes to strategic HRM and agile workforce planning by grounding theoretical concepts in real consulting practice, emphasizing the need to align autonomy with system support to achieve scalable, equitable, and responsive staffing.